Induction of long-term potentiation-like plasticity in the primary motor cortex with repeated anodal transcranial direct current stimulation – Better effects with intensified protocols? - Agboada, Desmond; Mosayebi-Samani, Mohsen; Kuo, Min-Fang; Nitsche, Michael A. (Brain stimulation, 2020)
A single session of anodal tDCS induces LTP-like plasticity which lasts for about 1 h, while repetition of stimulation within a time interval of 30 min results in late-phase effects lasting for at least 24 h with standard stimulation protocols. In this pilot study, we explored if the after-effects of a recently developed intensified single session stimulation protocol are relevantly prolonged in the motor cortex by repetition of this intervention. 16 healthy right-handed subjects participated in this study. The effects of an intensified (3 mA-20min) and a standard anodal tDCS protocol (1 mA-15min) with short (20 min) and long (3 h) repetition intervals were compared with the effects of respective single session tDCS protocols (3 mA-20min, 1 mA-15min, and Sham). Cortical excitability alterations were monitored by single-pulse TMS-elicited MEPs. Compared to sham, both single session tDCS protocols (1 mA-15min, and 3 mA-20min) resulted in cortical excitability enhancements lasting for about 30 min after stimulation. The short repetition interval (20 min) resulted in a prolongation of after-effects for the standard protocol, which lasted for more than 24 h after stimulation. For the intensified protocol, the prolongation of after-effects was limited to 120 min after stimulation. The long repetition interval (3 h) resulted in no excitability-enhancing after-effects for the intensified, and only minor excitability enhancement within the first 30 min after the intervention for the standard protocol. These results suggest a non-linearity of late-phase LTP-like plasticity induction, which was dependent not only on the interval of intervention repetition, but also on other protocol characteristics, including intensity, and duration of tDCS. Further studies in larger samples are needed to confirm these results. •With single session stimulation, both, standard and intensified protocols induced E-LTP-like plasticity.•Short-interval repetition resulted in L-LTP-like plasticity for the standard, but not the intensified tDCS protocol.•A repetition interval of 3 h did not induce L-LTP-like plasticity for standard and intensified protocols.